CIVILIAN-MILITARY INTERACTION ON THE MATIE CAMPUS: THE ‘BATTLE OF WILGENHOF’, 1957 - Visser, Deon (Scientia Militaria - South African Journal of Military Studies, 2011)
The South African Military Academy was established in 1950 as a branch of the SA Military College, under the academic auspices of the University of Pretoria. A mere three years later, in 1953, the Union Defence Force decided to relocate the Academy to Saldanha and to establish it as an independent military unit under the wings of Stellenbosch University. The relocation process took place during 1955/1956, shortly after construction of the Academy buildings at Saldanha had started. As a result, Stellenbosch University agreed to accommodate the Academy staff and students on the mother campus until the facilities at Saldanha were completed. However, not all civilian students welcomed the military students on the Matie campus, which culminated in the so-called ‘Battle of Wilgenhof’ in 1957. This article investigates the origins, extent, outcome and consequences of the conflict between military and civilian students on the campus of Stellenbosch University in the mid-1950s. It contends that the conflict was rooted in cultural rather than political differences, that the antagonism towards the military students was in essence restricted to the residents of Wilgenhof and that the ‘Battle of Wilgenhof’ had no lasting impact on the interaction between military and civilian students at Stellenbosch University.